Connections in steel structures III : behaviour, strength, and design : proceedings of the third international workshop held at Hotel Villa Madruzzo, Trento, Italy, 29-31 May 1995 - Bjorhovde, Reidar; Colson, Andre; Zandonini, Riccardo (Elsevier Science/ Elsevier Science, Inc., 1996)
This book publishes the proceedings from the Third International Workshop on Connections in Steel Structures: Behaviour, Strength and Design held in Trento, Italy, 29-31 May 1995. The workshop brought together the world's foremost experts in steel connections research, development, fabrication and design. The scope of the papers reflects state-of-the-art issues in all areas of endeavour, and manages to bring together the needs of researchers as well as designers and fabricators. Topics of particular importance include connections for composite (steel-concrete) structures, evaluation methods and reliability issues for semi-rigid connections and frames, and the impact of extreme loading events such as those imposed by major earthquakes. The book highlights novel methods and applications in the field and ensures that designers and other members of the construction industry gain access to the new results and procedures.